The Use of Interactive Learning Media to Enhance Interest in Science Learning in Elementary Schools - Azzahra Murthadila; Sonia Yulia Friska; Qonita Muhtya Qoirod; Susilawati; Selvia Desriani; Miftahul Jannah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Science learning in elementary schools plays a crucial role in developing students' critical thinking, logical reasoning, and curiosity about natural phenomena. However, science is often perceived as a difficult and less engaging subject due to the limited use of diverse instructional methods. This article aims to analyze how the use of interactive learning media can enhance students' interest in learning science at the elementary school level. The study employed a qualitative literature review approach by examining relevant national journal articles on the use of interactive media in science instruction. The findings indicate that interactive learning media, such as animated videos, simulations, and educational games, effectively increase students' engagement, motivation, and active participation during the learning process. Furthermore, the use of interactive media has been shown to facilitate students' understanding of abstract scientific concepts and significantly improve their learning outcomes. In conclusion, interactive learning media play a vital role in enhancing elementary school students' interest in science learning and represent an innovative solution for science education in the digital era.